Assistance for RM Riung Gunung Malino in Inventory Management for Sustainable Business - A. Besse Riyani Indah; Dwi Handayani; Diniary Ikasari Syamsul; Syarifuddin M Parenreng; Saiful .; Rosmalina Hanafi; Muhammad Rusman; Muhammad Facheruddin BJ; Dian Pratiwi Sahar; Nur Khaerani Busri (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
RM Riung Gunung Malino, located in Gowa, faces a major challenge in inventory management, as stock recording of raw materials and products is still carried out manually, making it difficult to monitor inventory accurately. This issue leads to overstocking or stock shortages, which reduce operational efficiency. This community service program was implemented to provide solutions through intensive assistance in structured and applicable inventory management training. The solutions offered include the implementation of a digital stock recording system using the inventory module in the Odoo application, the development of a more systematic manual format based on the concepts of safety stock, Reorder Point (ROP), and Economic Order Quantity (EOQ), as well as regular stock monitoring training. The results of the program show an improvement in the partner’s understanding and skills in managing inventory, as evidenced by the ability to create more organized stock records, calculate raw material needs, and determine reorder points accurately. The implemented recording system has proven effective in reducing the risk of stockouts and overstocking, thereby increasing operational efficiency. In addition, the partner has become more confident in managing their business sustainably. Thus, this program provides a tangible contribution to enhancing the competitiveness of culinary MSMEs while promoting business sustainability through effective and measurable inventory management.